2010 Second International Conference on Mobile, Hybrid, and on-Line Learning 2010
DOI: 10.1109/elml.2010.15
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Students' Own Mobile Devices and Rich Media: Two Case Studies from the Health Sciences

Abstract: Utilizing students' own mobile devices and rich media: Two case studies from the Utilizing students' own mobile devices and rich media: Two case studies from the health sciences health sciences

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…For example, Yahoo groups and wikis are used to discuss schoolwork while SNS capable of hosing video podcasts are being used for engagement, enhancing student attitudes and motivation (Andrews et al, 2010). SNS, such as Facebook, is easily accessible and easy to navigate and is used by students to ask questions related to their studies and for interactive learning (Greenhow & Robelia, 2009;Polsgrove & Frimming, 2013).…”
Section: Student Use Of Social Networkingmentioning
confidence: 99%
“…For example, Yahoo groups and wikis are used to discuss schoolwork while SNS capable of hosing video podcasts are being used for engagement, enhancing student attitudes and motivation (Andrews et al, 2010). SNS, such as Facebook, is easily accessible and easy to navigate and is used by students to ask questions related to their studies and for interactive learning (Greenhow & Robelia, 2009;Polsgrove & Frimming, 2013).…”
Section: Student Use Of Social Networkingmentioning
confidence: 99%
“…The majority of studies were of mixed methods design, combining both qualitative and quantitative research methods (19/21), whereas two studies used qualitative methodology (Reynolds & Fell, 2011; Tan et al, 2010). All studies except two included clearly defined aims and objectives (Andrews et al, 2010; McLeod et al, 2012). Assessment of the research quality found that 10 of the 21 studies scored 3/5, with the remainder scoring less than 3.…”
Section: Resultsmentioning
confidence: 99%
“…Reasons behind such scores were based upon factors such as lack of repeatability. For example, lack of detail regarding placement duration (Lin & Shen, 2013; Morris & Maynard, 2010), year group (MacKay & Harding, 2009), details of strategy usage (Pimmer et al, 2018), and sample size (Andrews et al, 2010). Only two studies included comparators as part of study methodology (Ladyshewsky & Gardner, 2008; Morley, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…This has therefore reduced the resource implication for the project significantly. With mobile devices now ubiquitous within the student body in academia, user-owned devices represent a great potential in utilizing technology for learning. , Additionally, students are generally au fait with their own mobile device and therefore do not require further training.…”
Section: Discussionmentioning
confidence: 99%